(untitled) (Semiárida, 2018)
Eleocharis maculosa (Vahl) Roem. & Schult. (Cyperaceae) is recorded for first time for La Pampa province. Geographic origin, life form and environment are briefly described. A key to differentiate it from the other species that grow in this province is given.